Foundations of ministry - Anthony, Michael J. (Wheaton, IL Bridgepoint, 1992)
Includes bibliographcial references.
Putting ministry in perspective / Michael J. Anthony -- The theology of Christian education / Daniel C. Stevens -- The history of Christian education / Daniel C. Stevens -- Philosophical foundations of ministry / Rex E. Johnson -- Foundations of human development / Dennis H. Dirks -- Psychological foundations of teaching in the local church / Shelly M. Cunningham -- Cross-cultural perspectives in Christian education / Reuben H. Brooks -- Moral and faith development in Christian education / Dennis H. Dirks -- The Christian education of children / Shelly M. Cunningham -- The Christian education of youth / Kenneth R. Garland -- The Christian education of adults / Rex E. Johnson -- Ministry to families in the local church / Judy K. TenElshof -- Ministry to single adults / Michael J. Anthony -- Organizational structures for Christian education ministry / Michael A. Bechtle -- The roles and responsibilities of Christian education personnel / Michael A. Bechtle -- Organizing Christian education ministry in the small church / Kenneth R. Garland -- Leadership recruitment and training / Kenneth R. Garland -- The role of women in leadership / Michael J. Anthony -- Legal and ethical issues in Christian education ministry / Kenneth R. Garland -- The ministry of Christian camping / Richard J. Leyda -- Parachurch ministries / Richard J. Leyda -- Counseling ministry in the church / Judy K. TenElshof -- Mission education in the local church / Reuben H. Brooks -- Special education ministries / Michael J. Anthony -- Public education, Christian schools, and home schooling / Michael J. Anthony.
Keywords: Christian education -- introductions